Myofibroma of the oral cavity mimicking a non-neoplastic inflammatory process: an unusual report - Rodrigues, Éwerton Daniel Rocha; Oliveira, Eder Magno Ferreira de; Ribeiro, Renato da Costa; Passador-Santos, Fabricio; Matos, Felipe Rodrigues de; Souza, Gustavo Almeida (Journal of Oral Diagnosis, 2020)
Myofibroma is a rare condition that is a benign neoplasm characterized by the proliferation of fusiform cells originated from myofibroblasts. A 9-year-old male patient presented a intraosseous lesion in the oral cavity, which caused mobility in two teeth within appro- ximately 1 month and was submitted to excisional biopsy. Microscopic analysis revealed fragments of neoplasia of mesenchymal origin, characterized by proliferation of spindle cells with eosinophilic staining, showing loose chromatin and indistinct cytoplasmic boundaries, as well as cells with vacuolated cytoplasm. The lesion was very cellular and organized into a bundle of intersecting neoplastic cells. In the immunohistochemical analysis, the proliferative index evaluated for the Ki-67 antibody was below 5%. Neoplas- tic cells were strongly positive for the smooth muscle actin antibody. Rare mitoses were observed in the specimen, leading to the diagnosis of myofibroma. After the diagnosis, the patient was referred to his pediatrician for investigation of possible myofibromatosis. After clinical and imaging analysis, no similar lesions were found, and the diagnosis of myofibromatosis was excluded. At 6 months postoperative, the patient returned to the outpatient clinic, without clinical and radiographic signs of recurrence and buccal tissues with normal appearance.